PENGARUH MODEL MIND MAPPING TERHADAP HASIL BELAJAR SISWA DALAM PEMBELAJARAN IPA KELAS IV DI SD NEGERI 1 PANANJUNG - Ai Nurhayati; Widdy Sukma Nugraha (Bale Aksara: Jurnal Pendidikan Sekolah Dasar, 2020)
The problem in this research is the learning outcomes of fourth grade students at SD Negeri 1 Pananjung. This study aims to determine the effect of mind mapping learning models on class IV student learning outcomes in science learning. The research method used was a quasi-experimental design with Nonequivalent Control Group Design. The sampling technique in this study is purposive sampling namely class IV A as an experimental group with 20 students and class IV B as a control group with 20 students, so the total sample in this study was 40 students. The instrument used was a multiple choice test instrument. The analysis technique used in this study is to use the t-test to find out whether the mind mapping learning model affects student learning outcomes or not. The results showed a mind mapping learning model significant effect on the learning outcomes of fourth grade students in learning science in SD Negeri 1 Pananjung on the subject of the discussion of energy sources. This is based on the results of the parametric inferential statistical test calculations, in the different test result show that there are differences differences in the value of tcount > ttable, where tcount > ttable or 4.63> 2.02 and the gain value in the experimental group is equal to 0,60 with moderate criteria. So it can be concluded that the application of the mind mapping learning model can affect the learning outcomes of fourth grade students in the cognitive aspects of science learning in SD Negeri 1 Pananjung.